Nature of The Atom (JOURNAL OF ADVANCES IN PHYSICS, 2019)
The atom as a subject is the most difficult of all subjects and for its many variations extremely large and the most incomprehensive of all phenomena. Nor so I fear will we ever come to a full understanding of it, nor even the half thereof. Yet we must make a start somewhere to learn the principle fashion of its nature and operation that for what I have seen is mostly misunderstood.I now am not enabled to reveal what exactly the atom is, nor how it precisely operates under all conditions, but I am able to grant us a more realistic look into the nature of the atomic nature.